2019
DOI: 10.1002/cnm.3256
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of hemodynamic alterations in pre‐ and post‐stenting cerebral aneurysms using a multiscale modeling

Abstract: The aim of this work was to use a multiscale modeling to study the influence of stent deployment, with generic stents, on flow distributions within the vascular network and the hemodynamic alterations within the cerebral aneurysms pre‐ and post‐stenting. To achieve this goal, two image‐based anatomical cerebral aneurysm models were reconstructed along with the respective aneurysms post‐stenting models after deploying a 16‐ or 24‐wire stent. The investigation results revealed that the stent may increase the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…To study the influences of the flow rate and shunt ratio on hemodynamic characteristics in ICASA models, two patient-specific cerebral aneurysm models (see Figure 1 ), i.e., (a) ICASA−1 (73-year-old, female), and (b) ICASA−2 (35-year-old, female), were built using an open source code, i.e., 3D Slicer, based on medical data provided by Miami Valley Hospital (Dayton, OH, USA) [ 47 , 48 ]. In the ICASA−1 model, the blood flows in through the ICA and flows out from the bifurcated distal arteries, i.e., posterior communicating artery (PComA) and ICA distal.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…To study the influences of the flow rate and shunt ratio on hemodynamic characteristics in ICASA models, two patient-specific cerebral aneurysm models (see Figure 1 ), i.e., (a) ICASA−1 (73-year-old, female), and (b) ICASA−2 (35-year-old, female), were built using an open source code, i.e., 3D Slicer, based on medical data provided by Miami Valley Hospital (Dayton, OH, USA) [ 47 , 48 ]. In the ICASA−1 model, the blood flows in through the ICA and flows out from the bifurcated distal arteries, i.e., posterior communicating artery (PComA) and ICA distal.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…To systematically investigate the PFR effects on the intra-hemodynamic characteristics in the ICASA models, three transient pulsatile flow rate waveforms (i.e., PFR−I, PFR−II, and PFR−III) with a period of = 1.0 s were applied as the boundary conditions at the ICA inlet (see Figure 3 ), representing cardiac PFR conditions. Specifically, the waveform of PFR−II is based on pulsatile flow rates obtained from a validated 1D model, which has been studied in our previous investigations [ 47 , 60 ]. According to a statistical study determining blood flow rates in cerebral arteries [ 26 ], another two waveforms, i.e., PFR−I and PFR−III, were generated by multiplying 0.57 and 1.43 times of PFR−II, respectively, which fall into the 95% confidence interval of blood flow rate in ICA based on statistics [ 26 ].…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies, including aneurysm clipping or embolization, stent implantation were used to reduce IAP, which avoided aneurysm rupture intraoperatively and reduced aneurysm recurrence and rupture postoperatively. Yu and colleagues ( 52 ) investigated the hemodynamic changes in pre-and-post stenting of aneurysms and found that stent placement can reduce IAP and WSS at the neck region in side-wall aneurysms. In another investigation ( 53 ), the 4 different stents (LVIS, LVIS Jr, Leo, Barrel VRD) showed IAP decreased significantly after stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have focused on the simulation of the mechanical deployment of flow-diverter stents using finite element analysis to capture the clinically realistic FD deployment processes [3,13]. Some researchers have conducted stent deployment and CFD simulations simultaneously to investigate the influence of different stent deployment approaches and the location of stents on the hemodynamics of aneurysms by comparing untreated and stented vessels [9,14,15]. It is noted that the specifications of FD stents such as stent type, mesh porosity, and mesh pore density are other determining factors in the greater device efficacy, which have been considered by researchers using CFD simulations [6,8,16].…”
Section: Introductionmentioning
confidence: 99%